Sesquiterpene coumarin ethers with selective cytotoxic activities from the roots of ferula huber-morathii Peşmen (Apiaceae) and unequivocal determination of the absolute stereochemistry of samarcandin - Eruçar, Fatma Memnune; Kuran, Fadıl Kaan; Altıparmak Ülbegi, Gülsüm; Özbey, Süheyla; Karavuş, Şule Nur; Arcan, Gülşah Gamze; Yazıcı Tütüniş, Seçil; Tan, Nur; Aksoy Sağırlı, Pınar; Miski, Mahmut (MDPI, 2023)
Ancient physicians frequently used the resin of Ferula species to treat cancer. Today, some folkloric recipes used for cancer treatment also contain the resin of Ferula species. The dichloromethane extract of the roots of Ferula huber-morathii exhibited cytotoxic activities against COLO 205 (colon), K-562 (lymphoblast), and MCF-7 (breast) cancer cell lines (IC50 = 52 µg/mL, 72 µg/mL, and 20 µg/mL, respectively). Fifteen sesquiterpene coumarin ethers with cytotoxic activity were isolated from the dichloromethane extract of the roots of F. huber-morathii using bioactivity-directed isolation studies. Extensive spectroscopic analyses and chemical transformations have elucidated the structures of these sesquiterpene coumarin ethers as conferone (1), conferol (2), feselol (3), badrakemone (4), mogoltadone (5), farnesiferol A (6), farnesiferol A acetate (7), gummosin (8), ferukrin (9), ferukrin acetate (10), deacetylkellerin (11), kellerin (12), samarcandone (13), samarcandin (14), and samarcandin acetate (15). The absolute configuration of samarcandin (14) was unequivocally determined by the X-ray crystallographic analysis of the semi-synthetic (R)-MTPA ester of samarcandin (24). Conferol (2) and mogoltadone (5) were found to be the most potent cytotoxic compounds against all three cancer cell lines; furthermore, these compounds exhibit low cytotoxic activity against the non-cancerous human umbilical vein epithelial cells (HUVEC) cell line. Investigation of the biological activity mechanisms of mogoltadone (5) revealed that while suppressing the levels of Bcl-XL and procaspase-3 in the COLO 205 cancer cell line, it did not have a significant effect on the Bcl-XL, caspase-3, and ?-catenin protein levels of the HUVEC cell line, which may explain the cytotoxic selectivity of mogoltadone (5) on cancer cell lines.
Keywords: Ferula Huber-Morathii; Sesquiterpene Coumarin Ethers; Cytotoxicity; COLO 205; MCF-7; K-562; Bcl-XL; Caspase 3, 8, 9; ?-Catenin; Molecular Docking